Seeds of a Revolution: Land Reform and Literary Ecologies in Modern Latin American Literature - Kolijn, Adriana (Université d'Ottawa | University of Ottawa, 2026)
This dissertation seeks to establish the connections between ecological and socio-political well being in the context of contemporary Latin America. It investigates the ecological aspirations of calls for land reform in many of the revolutions rocking the continent in the 20th century. Questions concerning land management came to the fore, and the policies developed in answer to these problems continue to have long lasting impacts still felt today. Ever since the end of the Mexican Revolution in 1917, Mexican governments have hailed it as a success. However, the short story collection El llano en llamas (1953) by Juan Rulfo and the novel Temporada de huracanes (2017) by Fernanda Melchor portray a very different reality faced by rural populations and landscapes. I argue that these texts explore how the failure of revolutionary policies, in particular the Agrarian Reform, marginalize the human and natural world. In their portrayal of rural Mexico, Rulfo’s short stories and Melchor’s novel critique the Mexican State and show how poor policy design affects both local societies as well as ecologies. In Guatemala, the October Revolution (1944-1954) provided the country with ten years of democratic rule. Published in this time, Hombres de maíz (1949) by Miguel Ángel Asturias presented a hopeful and critical reflection on the beginnings of the so-called ten years of Spring. Seven decades later, El país de Toó (2018) by Rodrigo Rey Rosa shows that dreams of a revolution reawaken in the face of ongoing corruption and impunity. Reading these two texts together through an ecocritical framework, I explore how both texts engage with the Mayan cosmovision and signal the importance of ecological and social reconciliation in order to heal a country’s society and environment. Finally, in Nicaragua, the victory of the Sandinista Revolution (1979-1990) culminated in the ousting of American sponsored dictator Anastasio Somoza. The decisive and complete victory of the Sandinistas provided Nicaraguan intellectuals and its followers with a unique opportunity to forge a new national identity, affirm national sovereignty and create policies responsive to the needs of the ordinary Nicaraguan. The two authors Ernesto Cardenal and Gioconda Belli participated in this project both as revolutionary leaders and literary visionaries. My analysis of Cardenal’s Cántico cósmico (1989) and Belli’s Waslala (1996) explores the connections between social and environmental issues as well as how their shared utopian impulse can inspire future generations and remind readers of how this initial moment formed the social, ecological and political laboratory that was the Sandinista Revolution.
Keywords: Ecocriticism; Land Reform; Modern Latin American Literature; Revolutions; Holistic Reconciliation; Sacrifice Zones; Slow Violence